POLA NYERI PASIEN PENYAKIT PARKINSON DI POLIKLINIK SARAF RSUP dr HASAN SADIKIN BANDUNG - Nino Widjayanto, Thamrin Syamsudin, Henny Anggraini Sadeli (NEURONA, 2013)
INTRODUCTION PAIN IS A NONMOTOR MANIFESTATION IN PARKINSONS DISEASE PD WITH PREVALENCE VARIES IN SOME STUDIES BETWEEN 4080 PAIN IN PD MAY INCLUDE NOCICEPTIVE AND NEUROPATHIC PAIN NOCICEPTIVE PAIN SUCH AS MUSCULOSKELETAL PAIN AND DYSTONIARELATED PAIN AND NEUROPATHIC RADICULAR PAIN ARE SECONDARY TO MOTOR MANIFESTATIONS BRADIKINESIA RIGIDITY AND POSTURAL DISORDERS CENTRAL NEUROPATHIC PAIN IS A PRIMARY FORM DUE TO DEGENERATION IN THE BASAL GANGLIA AND SYSTEMS ASSOCIATED WITH PAIN THE INCIDENCE OF MUSCULOSKELETAL PAIN IN PD PATIENTS WAS HIGHER COMPARED TO THE NORMAL POPULATION OF THE SAME AGE